Suttonella ornithocola detected within lesions of tit birds (Paridae) from epidemic death episodes in Germany, 2018–2020 - Leitzen, Eva; Peters, Martin; Merbach, Sabine; Wohlsein, Peter; Baumgärtner, Wolfgang (Frontiers in Veterinary Science, 2022)
Several episodes of increased mortality in wild birds of the families Paridae and Aegithalidae have been documented in recent decades. The majority of affected animals exhibited necrotizing pneumonia with intralesional bacteria. Suttonella (S.) ornithocola, a Gram-negative bacterium in the Cardiobacteriaceae family, has been regularly cultured bacteriologically from affected birds and has long been suspected as a potentially fatal cause of respiratory disease in birds. However, a direct causal relationship between this specific bacterium and the observed lesions within birds has not yet been established. Therefore, within the present study, postmortem tissue from five tits, including 3 blue (Cyanistes caeruleus) and 2 great tits (Parus major) that were tested positive for S. ornithocola in bacteriological examination, originating from two incidents of increased mortality in Paridae in Germany was used. Animals found dead in the administrative district of Arnsberg (North Rhine Westphalia) in 2018 and 2020 were investigated for genomic fragments of S. ornithocola by chromogenic in situ hybridization using a newly developed DNA probe based on publicly assessable DNA sequences of the 16S rRNA gene of S. ornithocola. Positive hybridization signals were detected in 4 of the 5 animals and were predominantly detected within necrotizing lesions in lung and occasionally in lesions affecting liver and trachea. Interestingly, the lung of one animal without obvious necrotizing pulmonary lesions revealed positive hybridization results in the lumen of one pulmonary blood vessel. Two negative controls, including one bacteriologically S. ornithocola-negative great tit and a cattle egrit suffering from salmonellosis, did not yield positive signals, indicating high sensitivity and specificity of the probe used. This is the first time that S. ornithocola has been clearly identified within necrotizing lesions in deceased tits. Although Koch's postulates have yet to be fulfilled, positive hybridization signals in association with detectable lesions can be considered as further and strong evidence of the significant contribution of S. ornithocola to the several episodes of tit mortality recorded in Germany and the United Kingdom.